Cyclosporin neurotoxicity in cardiac transplant recipients. Issue 11 (November 1988) - Lane, R J; Roche, S W; Leung, A A; Greco, A; Lange, L S
Abstract : Cyclosporin toxicity may produce a wide range of neurological disorders. We report three patients whose neurological problems developed while taking cyclosporin following cardiac transplantation, but resolved rapidly when the drug was discontinued. In two cases, MRI revealed abnormalities which disappeared with clinical recovery. Blood cyclosporin concentrations were not markedly increased, and it is possible that the neurotoxic effects of cyclosporin are mediated by metabolites, through an effect on the blood-brain barrier.